Intermetallic compound nano material as well as preparation method and application thereof

By preparing hexagonal intermetallic nanomaterials composed of Pt, Pb, and Sn, the process was simplified by the solvent-thermal reaction method, the problem of insufficient activity and stability of Pt-based electrocatalysts was solved, and the efficient catalytic performance in alcohol oxidation reaction was achieved and stability, suitable for large-scale applications.

CN119133481AActive Publication Date: 2024-12-13WUYI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411168668.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2024-12-13
Estimated Expiration
2044-08-23

AI Technical Summary

Technical Problem

The existing Pt-based electrocatalysts have problems with insufficient catalytic activity and stability in alcohol oxidation reactions, especially those susceptible to intermediate product CO poisoning, resulting in limited long-term catalytic efficiency and stability, and the preparation method is complex and time-consuming, which is limited. Its promotion in practical applications.

Method used

A hexagonal intermetallic compound nanomaterial composed of Pt, Pb, and Sn is used to prepare by solvothermal reaction method, simplifying the process conditions, realizing the regulation of Pt electronic structure and improving the catalytic reaction performance.

Benefits of technology

This nanomaterial exhibits high catalytic activity and stability in alcohol oxidation reaction, with a mass activity of 9200mA·g-1, and is simple in preparation, suitable for large-scale production, and maintains excellent catalytic performance during long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133481A_ABST
    Figure CN119133481A_ABST
Patent Text Reader

Abstract

The invention discloses an intermetallic compound nano-material and a preparation method and application thereof, the intermetallic compound nano-material is in a hexagonal prism shape, is composed of three elements of Pt, Pb and Sn, has a PtPb phase structure, and shows catalytic activity and stability far superior to those of a commercial Pd / C catalyst in an alcohol oxidation reaction. The invention provides the efficient and simple preparation method of the intermetallic compound nano material, the method adopts a one-step solvothermal synthesis strategy, the process flow is simple, the nano material with highly consistent size and excellent dispersity can be prepared, and the method is suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalyst materials, and in particular relates to an intermetallic compound nanomaterial and a preparation method and application thereof. Background Art

[0002] As a cutting-edge energy conversion technology, direct alcohol fuel cells (DAFCs) have the unique advantage of being able to directly use alcohols (such as methanol, ethanol, etc.) as fuel and efficiently convert them into electrical energy through the oxidation reaction at the anode, eliminating the complex reforming step in traditional fuel cells and greatly improving the efficiency and convenience of energy conversion. In this process, the alcohol oxidation reaction occurring at the anode is the key link that determines the overall performance and efficiency of DAFCs. Highly active and durable catalysts are necessary to ensure the performance of alcohol electrooxidation. At present, precious metal platinum (Pt) is widely used as a catalyst for alcohol oxidation due to its excellent catalytic performance. However, the scarcity and high cost of Pt hinder its large-scale application. In addition, Pt is prone to form strong chemical bonds with certain intermediates (such as CO) during the catalytic process, resulting in catalyst poisoning and occupation of active sites, which seriously limits its long-term catalytic efficiency and stability. In response to the above problems, current research focuses on the development of new and efficient Pt-based electrocatalysts, aiming to improve their catalytic activity for alcohol oxidation, anti-poisoning ability, and ability to promote CC bond cleavage.

[0003] The construction of ordered intermetallic compounds can improve both the catalytic activity and stability of catalysts, which is mainly due to their unique electronic structure and chemical properties. Compared with alloys, intermetallic compounds have higher mixing enthalpy and stronger interatomic interactions, which provides a basis for changing the electronic structure by adjusting the arrangement and bonding mode of metal atoms, thereby promoting the catalytic kinetics of Pt and improving the electrocatalytic performance. More importantly, intermetallic compounds have a fixed crystal structure, which is convenient for identifying and analyzing the real active sites in the catalytic reaction, and lays a foundation for exploring the catalytic mechanism and establishing the structure-performance relationship. However, although a variety of methods such as high-temperature melting method, mechanical alloying method, sol-gel method and chemical vapor deposition method have been reported for the synthesis of intermetallic compounds, most of these methods face challenges such as complex operation, harsh conditions (such as high temperature and high pressure), and long time consumption, which limits their promotion in practical applications. Therefore, it is crucial to explore simple and easy methods for preparing Pt-based intermetallic compounds, realize the regulation of Pt electronic structure, and optimize its binding energy with catalytic reactants and intermediates for the development of highly active and stable Pt-based alcohol oxidation catalysts. Summary of the invention

[0004] In order to overcome the problems existing in the above-mentioned prior art, one of the purposes of the present invention is to provide an intermetallic compound nanomaterial. The second purpose of the present invention is to provide a method for preparing the above-mentioned intermetallic compound nanomaterial. The third purpose of the present invention is to provide an application of the above-mentioned intermetallic compound nanomaterial.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] A first aspect of the present invention provides an intermetallic compound nanomaterial, which is in the shape of a hexagonal prism, is composed of three elements: Pt, Pb, and Sn, and has a PtPb phase structure.

[0007] Preferably, the mass fractions of the Pt, Pb and Sn elements are 40-45%, 42-47% and 9-14% respectively.

[0008] Preferably, the particle size of the intermetallic compound nanomaterial is 10-100 nm.

[0009] The second aspect of the present invention provides a method for preparing the intermetallic compound nanomaterial described in the first aspect, characterized in that it comprises the following steps: mixing a reducing organic solvent, a reducing agent, a platinum source, a lead source and a tin source, and performing a solvothermal reaction to obtain the intermetallic compound nanomaterial.

[0010] Preferably, the reducing organic solvent is selected from one or more of oleylamine, oleic acid, tetradecene and octadecene.

[0011] More preferably, the reducing organic solvent is selected from oleylamine and octadecene.

[0012] More preferably, the volume ratio of oleylamine to octadecene is (1-2):1.

[0013] Preferably, the reducing agent is selected from glucose.

[0014] Preferably, the platinum source is selected from one or more of platinum acetylacetonate, platinum chloroplatinic acid, potassium chloroplatinate, and potassium chloroplatinite.

[0015] Preferably, the lead source is selected from one or more of lead acetylacetonate, lead nitrate, lead acetate or lead chloride.

[0016] Preferably, the tin source is selected from one or more of tin chloride, stannous chloride, tin chloride pentahydrate, stannous chloride dihydrate, and potassium stannate.

[0017] Preferably, the molar ratio of the platinum source to the lead source is 1:(0.5-1).

[0018] More preferably, the molar ratio of the platinum source to the lead source is 1:(0.7-0.9).

[0019] Preferably, the molar ratio of the platinum source to the tin source is 1:(0.2-0.5).

[0020] More preferably, the molar ratio of the platinum source to the tin source is 1:(0.3-0.5).

[0021] Preferably, the molar ratio of the platinum source to the reducing agent is 1:(1-10).

[0022] Preferably, the usage ratio of the platinum source to the reducing organic solvent is (0.003-0.007) mmol:1 mL.

[0023] Preferably, the reaction temperature of the solvothermal reaction is 160-200°C.

[0024] More preferably, the reaction temperature of the solvothermal reaction is 170-190°C.

[0025] Preferably, the reaction time of the solvent thermal reaction is 4 to 8 hours.

[0026] More preferably, the reaction time of the solvothermal reaction is 4 to 6 hours.

[0027] The third aspect of the present invention provides the use of the intermetallic compound nanomaterial described in the first aspect in the preparation of an alcohol oxidation catalyst.

[0028] Preferably, the intermetallic compound nanomaterial is used in the preparation of an ethanol oxidation catalyst.

[0029] The beneficial effects of the present invention are:

[0030] 1. The present invention provides an intermetallic compound nanomaterial, which is in the shape of a hexagonal prism and is composed of three elements: Pt, Pb, and Sn. It has a PtPb phase structure. The nanomaterial exhibits excellent catalytic reaction performance in alcohol oxidation reaction and has extremely high catalytic activity (mass activity up to 9200 mA g) compared with commercial Pt / C catalysts. -1 ) and stability. In addition, the nanomaterial also has high EOR catalytic stability.

[0031] 2. The present invention also provides a method for preparing the above-mentioned intermetallic compound nanomaterials. The intermetallic compound nanomaterials can be prepared by a simple one-step solvothermal method. The preparation process does not involve high temperature and high pressure reaction conditions, nor does it require long-term ball milling. The preparation process is simple, and the prepared nanomaterials are of relatively uniform size and evenly dispersed, which is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1is the X-ray diffraction pattern of the SnPbPt samples of Example 1 and Comparative Examples 1-4;

[0033] Figure 2 is the X-ray diffraction pattern of the SnPbPt sample of Example 1 after being placed at room temperature for two months;

[0034] Figure 3 is a transmission electron microscope image of the SnPbPt sample of Example 1;

[0035] Figure 4 is the element distribution diagram of the SnPbPt sample of Example 1;

[0036] Figure 5 is an X-ray energy spectrum analysis diagram of the SnPbPt sample of Example 1;

[0037] Figure 6 is a scanning electron microscope image of the SnPbPt sample of Example 1;

[0038] Figure 7 is a scanning electron microscope image of the SnPbPt sample of Comparative Example 1;

[0039] Figure 8 is a scanning electron microscope image of the SnPbPt sample of Comparative Example 2;

[0040] Fig. 9 is a scanning electron microscope image of the SnPbPt sample of Comparative Example 3;

[0041] Fig.10 is a scanning electron microscope image of the SnPbPt sample of Comparative Example 4;

[0042] Fig.11 CV curve of the SnPbPt sample modified electrode in Example 1 and the CV curve after 1000 cycles;

[0043] Fig.12 is the CV curve of the SnPbPt sample modified electrode of Comparative Example 1;

[0044] Fig.13 is the CV curve of the SnPbPt sample modified electrode of Comparative Example 2;

[0045] Fig.14 is the CV curve of the SnPbPt sample modified electrode of Comparative Example 3;

[0046] Fig.15 This is the CV curve of the SnPbPt sample modified electrode of Comparative Example 4. DETAILED DESCRIPTION

[0047] The present invention is further described in detail below through specific examples. The raw materials used in the following examples, unless otherwise specified, can be obtained from conventional commercial sources or prepared and separated by simple synthesis; the processes used, unless otherwise specified, are conventional processes in the art.

[0048] Example 1

[0049] This embodiment provides an intermetallic compound nanomaterial, and the preparation method is as follows:

[0050] 3 mL of oleylamine, 2 mL of octadecene, 30 mg of glucose, 0.025 mmol of platinum acetylacetonate, 0.02 mmol of lead acetylacetonate and 0.01 mmol of anhydrous stannous chloride were placed in a round-bottom flask, and the raw materials were dissolved by ultrasound. The mixed solution was heated to 180°C and reacted at this temperature for 5 hours. After the reaction was completed, the product was collected by centrifugation at 15,000 rpm for 5 minutes. Finally, the product was washed with ethanol and cyclohexane for 4 to 6 times, and dried at 60°C to obtain an intermetallic compound nanomaterial, recorded as SnPbPt.

[0051] Comparative Example 1

[0052] This embodiment provides an intermetallic compound nanomaterial, and the preparation method is as follows:

[0053] 3 mL of oleylamine, 2 mL of octadecene, 30 mg of glucose, 0.025 mmol of platinum acetylacetonate, 0.02 mmol of lead acetylacetonate and 0.01 mmol of anhydrous stannous chloride were placed in a round-bottom flask, and the raw materials were dissolved by ultrasound. The mixed solution was heated to 120°C and reacted at this temperature for 5 hours. After the reaction was completed, the product was collected by centrifugation at 15,000 rpm for 5 minutes. Finally, the product was washed with ethanol and cyclohexane for 4 to 6 times, and dried at 60°C to obtain an intermetallic compound nanomaterial.

[0054] Comparative Example 2

[0055] This embodiment provides an intermetallic compound nanomaterial, and the preparation method is as follows:

[0056] 3 mL of oleylamine, 2 mL of octadecene, 30 mg of glucose, 0.025 mmol of platinum acetylacetonate, 0.02 mmol of lead acetylacetonate and 0.01 mmol of anhydrous stannous chloride were placed in a round-bottom flask, and the raw materials were dissolved by ultrasound. The mixed solution was heated to 150°C and reacted at this temperature for 5 hours. After the reaction was completed, the product was collected by centrifugation at 15,000 rpm for 5 minutes. Finally, the product was washed with ethanol and cyclohexane for 4 to 6 times, and dried at 60°C to obtain an intermetallic compound nanomaterial.

[0057] Comparative Example 3

[0058] This embodiment provides an intermetallic compound nanomaterial, and the preparation method is as follows:

[0059] 3 mL of oleylamine, 2 mL of octadecene, 30 mg of glucose, 0.0125 mmol of platinum acetylacetonate, 0.02 mmol of lead acetylacetonate and 0.01 mmol of anhydrous stannous chloride were placed in a round-bottom flask, and the raw materials were dissolved by ultrasound. The mixed solution was heated to 180°C and reacted at this temperature for 5 hours. After the reaction was completed, the product was collected by centrifugation at 15,000 rpm for 5 minutes. Finally, the product was washed with ethanol and cyclohexane for 4 to 6 times, and dried at 60°C to obtain an intermetallic compound nanomaterial.

[0060] Comparative Example 4

[0061] This embodiment provides an intermetallic compound nanomaterial, and the preparation method is as follows:

[0062] 3 mL of oleylamine, 2 mL of octadecene, 30 mg of glucose, 0.025 mmol of platinum acetylacetonate, 0.01 mmol of lead acetylacetonate and 0.01 mmol of anhydrous stannous chloride were placed in a round-bottom flask, and the raw materials were dissolved by ultrasound. The mixed solution was heated to 180°C and reacted at this temperature for 5 hours. After the reaction was completed, the product was collected by centrifugation at 15,000 rpm for 5 minutes. Finally, the product was washed with ethanol and cyclohexane for 4 to 6 times, and dried at 60°C to obtain an intermetallic compound nanomaterial.

[0063] Material characterization

[0064] Figure 1 It is the X-ray diffraction pattern (XRD) of the SnPbPt samples of Example 1 and Comparative Examples 1-4. The SnPbPt sample of Example 1 is an intermetallic compound of the PbPt (JCPDS06-0374) phase. There is no Sn diffraction peak in XRD, which is speculated to be due to too little Sn content. The intensity of the characteristic peaks of the samples of Comparative Examples 1-4 is low, or inconsistent with the standard card, indicating that different metal source concentrations and temperatures have a certain influence on the intermetallic compounds of the sample SnPbPt.

[0065] Figure 2 This is the X-ray diffraction pattern of the SnPbPt sample of Example 1 after being placed at room temperature for two months. The structure of SnPbPt has not changed after being placed at room temperature for two months, indicating the stability of the SnPbPt structure.

[0066] Figure 3 It is a transmission electron microscope image of the SnPbPt sample of Example 1. The particle morphology of the SnPbPt sample is hexagonal prism.

[0067] Figure 4 and Figure 5They are the element distribution diagram and X-ray energy spectrum analysis (EDS) diagram of the SnPbPt sample of Example 1, and the SnPbPt sample of Example 1 is also subjected to an inductively coupled plasma (ICP) test, and the results are shown in Table 1:

[0068] Table 1

[0069]

[0070] from Figure 4 , Figure 5 It can be concluded from Table 1 that the intermetallic compound nanomaterial is composed of three elements: Pt, Pb and Sn.

[0071] Figure 6 is a scanning electron microscope image of the SnPbPt sample of Example 1; Figure 7 is a scanning electron microscope image of the SnPbPt sample of Comparative Example 1; Figure 8 is a scanning electron microscope image of the SnPbPt sample of Comparative Example 2; Fig. 9 is a scanning electron microscope image of the SnPbPt sample of Comparative Example 3; Fig.10 This is a scanning electron microscope image of the SnPbPt sample of Comparative Example 4; Figure 7-8 It can be seen that in Comparative Examples 1 and 2, when the temperature is not high enough, SnPbPt fails to completely form a hexagonal core-shell structure intermetallic compound. As the temperature gradually increases, the morphology of SnPbPt changes from a triangular prism to a hexagonal prism. The product obtained in Example 1 has a more uniform size and is evenly dispersed. Figure 9-10 It can be seen that under different metal source concentrations, SnPbPt fails to form hexagonal prism-shaped intermetallic compounds, but forms a morphology with small particles on a sphere.

[0072] Experimental analysis

[0073] The products of Example 1 and Comparative Examples 1-4, as well as commercial Pd / C catalyst (commercial Pd) were tested for ethanol oxidation catalytic performance. The specific test methods and results are as follows:

[0074] 1. The test method includes the following steps: (1) Preparation of the working electrode: The glassy carbon electrode (GCE) modified by the experimentally synthesized sample is prepared by ultrasonically dispersing 1 mg of the dried product of Example 1 and Comparative Examples 1-4 in 1 mL of pure water, taking 10 μL of the dispersion and evenly dropping it on the cleaned GCE surface, exposing it to an infrared lamp for drying before subsequent testing. (2) Test conditions: A three-electrode test method is used, with a glassy carbon electrode coated with a catalyst as the working electrode, a reference electrode of mercury / mercuric oxide, a counter electrode of a Pt sheet, and an electrolyte of 1.0 mol / L KOH and 1.0 mol / L ethanol aqueous solution, and the test is carried out. The CV test interval is -0.97 V to 0.3 V, and the scanning speed is 50 mV / s.

[0075] 2. Fig.11 CV curve of the SnPbPt sample modified electrode in Example 1 and the CV curve after 1000 cycles; Fig.12 is the CV curve of the SnPbPt sample modified electrode of Comparative Example 1; Fig.13 is the CV curve of the SnPbPt sample modified electrode of Comparative Example 2; Fig.14 is the CV curve of the SnPbPt sample modified electrode of Comparative Example 3; Fig.15 This is the CV curve of the SnPbPt sample modified electrode of Comparative Example 4. Figure 11-15 It can be seen that the peak voltage of the SnPbPt modified electrode of Example 1 is -0.097V (relative to mercury / mercuric oxide), and the peak current density is about 9222.1mA / g. The peak voltage of commercial Pd / C is -0.153V, and the peak current density is 543.7mA / g. The peak current density of the SnPbPt modified electrode of Example 1 is 17 times that of Pd / C. The peak current densities of Comparative Examples 1-4 are not as good as those of the SnPbPt modified electrode of Example 1, indicating that the SnPbPt modified electrode of Example 1 has high catalytic activity for ethanol oxidation reaction. In addition, from Fig.11 It can be seen that after 1000 CV cycles, the current density of the SnPbPt modified electrode of Example 1 is 2825.5 mA / g, which is still much higher than that of commercial Pd / C, indicating that SnPbPt has good cycle stability.

[0076] The above is a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.

Claims

1. An intermetallic compound nanomaterial, characterized in that: The intermetallic compound nanomaterial is in the shape of a hexagonal column, is composed of three elements, namely Pt, Pb and Sn, and has a PtPb phase structure.

2. The intermetallic compound nanomaterial according to claim 1, characterized in that: The mass fractions of the Pt, Pb and Sn elements are 40-45%, 42-47% and 9-14% respectively.

3. The intermetallic compound nanomaterial according to claim 1, characterized in that: The particle size of the intermetallic compound nanomaterial is 10-100 nm.

4. The method for preparing the intermetallic compound nanomaterial according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: mixing a reducing organic solvent, a reducing agent, a platinum source, a lead source and a tin source, and performing a solvent thermal reaction to obtain the intermetallic compound nano material.

5. The method for preparing the intermetallic compound nanomaterial according to claim 4, characterized in that: The reducing organic solvent is selected from one or more of oleylamine, oleic acid, tetradecene and octadecene.

6. The method for preparing the intermetallic compound nanomaterial according to claim 4, characterized in that: The reducing agent is selected from glucose.

7. The method for preparing an intermetallic compound nanomaterial according to claim 4, characterized in that: The platinum source is selected from one or more of platinum acetylacetonate, platinum chloroplatinic acid, potassium chloroplatinate, and potassium chloroplatinite; And / or, the lead source is selected from one or more of lead acetylacetonate, lead nitrate, lead acetate or lead chloride; And / or, the tin source is selected from one or more of tin chloride, stannous chloride, tin chloride pentahydrate, stannous chloride dihydrate, and potassium stannate.

8. The method for preparing an intermetallic compound nanomaterial according to claim 4, characterized in that: The molar ratio of the platinum source to the lead source is 1:(0.5-1); And / or, the molar ratio of the platinum source to the tin source is 1:(0.2-0.5).

9. The method for preparing an intermetallic compound nanomaterial according to claim 4, characterized in that: The reaction temperature of the solvent thermal reaction is 160-200°C.

10. Use of the intermetallic compound nanomaterial according to any one of claims 1 to 3 in the preparation of an alcohol oxidation catalyst.

Citation Information

Patent Citations

  • One-dimensional porous platinum-containing alloy nanowire catalyst and preparation method thereof

    CN111509236A

  • Atmosphere control preparation method of platinum-tin intermetallic compound nano-catalyst

    CN112481632A

  • Intermetallic compound catalyst with high catalytic activity as well as preparation method and application thereof

    CN118147701A